A 6DOF passive vibration isolator using X-shape supporting structures. (13th October 2016) - Wu, Zhijing; Jing, Xingjian; Sun, Bo; Li, Fengming
Abstract: A novel 6 degree of freedom (6-DOF) passive vibration isolator is studied theoretically and validated with experiments. Based on the Stewart platform configuration, the 6-DOF isolator is constructed by 6 X-shape structures as legs, which can realize very good and tunable vibration isolation performance in all 6 directions with a passive manner. The mechanic model is established for static analysis of the working range, static stiffness and loading capacity. Thereafter, the equation of motion of the isolator is derived with the Hamilton principle. The equivalent stiffness and the displacement transmissibility in the six decoupled DOFs direction are then discussed with experimental results for validation. The results reveal that (a) by designing the structure parameters, the system can possess flexible stiffness such as negative, quasi-zero and positive stiffness, (b) due to the combination of the Stewart platform and the X-shape structure, the system can have very good vibration isolation performance in all the 6 directions and in a passive manner, and (c) compared with the simplified linear-stiffness legs, the nonlinearity of the X-shape structures enhance the passive isolator to have much better vibration isolation performance. Highlights: The Stewart platform is constructed with X-shape structures. The new platform can achieve excellent passive isolation performance in all 6 directions. The nonlinearity introduced by the X-shape structures greatly enhances the performance. Prototype design and experimental results validate the theoretical analysis.